ANALISIS PERBANDINGAN KUALITAS PROMOSI, KERAGAMAN PRODUK DAN KEMUDAHAN PENGGUNAAN ANTARA E-COMMERCE SHOPEE DAN TOKOPEDIA - Natallia Glori; William Widjaja (Bina Ekonomi, 2024)
Shopping online through e-commerce in Indonesia is currently growing rapidly. Such as Shopee, Tokopedia, Lazada, Bukalapak, Bli-bli and more. The purpose of this research is to find out whether there are differences in promotion, product diversity and ease of use between Shopee and Tokopedia, which are the pioneers of e-commerce in Indonesia. This research is included in the type of comparative research using quantitative methods. Data collections using a questionnaire with a Likert scale. The number of respondents reached was 300 respondents with a distribution of 150 respondents for each object. The sampling used in this research is purposive sampling which is included in non-probability sampling. While the analysis used is the Mann Whitney difference test with the help of SPSS software version 25. The results showed that only the promotion variable has a significant difference between Shopee and Tokopedia or Ho is accepted, with a significance of 0.04 which is less than 0.050. As for the variables of product diversity and ease of use, there is no significant difference. Each has a significance value of 0.326 for product diversity and 0.432 for ease of use which is greater than 0.050 so that Ho is rejected.